Ruptura de pares y efectos coulombianos en la fisión fría de las reacciones 233U(NTH, F), 235U(NTH, F) Y 239Pu(NTH, F) - Montoya, Modesto (2013)
This paper shows pair breaking and electrostatic (Coulomb) interaction effects on the distribution of mass and kinetic energy in cold fission of 233U, 235U and 239Pu thermal neutron induced. The fission process ends at the scission point, when the complementary fragments 1 and 2, having masses y A1A2 are formed. Those fragments goes away each other and acquire kinetic energies y E1E2. The fragments emit neutrons eroding mass and kinetic energy distribution. In order to avoid these disturbances, cold fission, i.e. with no neutron emission, is studied. Contrary to expected, for that excitation energy region, tough weak, an even-odd effect is observed.This result is not incompatible with a strong odd-even effect on the charge distribution or neutron number distribution. Moreover In cold fission, the minimum value of total excitation energy ( ), as a function of , is correlated with the "Coulomb energy excess" defined as the difference between the energy electrostatic interaction of the complementary fragments (assumed spherical) in the scission point and the available energy of the reaction. This also explains correlation fluctuations in the maximum kinetic energy as a function of the mass. This effect increases with the asymmetry of the charge fragmentations. In sum, the experimental data on cold fission suggest that scission configurations explore all the possibilities available energy for fission.